Advances in digital marketing in the era of artificial intelligence : case studies and data analysis for business problem solving - Ltifi, Moez (CRC Press, 2024)
"This book highlights the technological advances that are transforming the future of digital marketing and covers important areas of research in this field. The book demonstrates advances in digital marketing as well as tools, techniques, methods and strategies based on artificial intelligence. It also identifies gaps in research into effective digital marketing tools, techniques and methods, and will bridge the interaction between digital marketing strategies and organizations' business plans on the one hand, and customer relations on the other, in the age of artificial intelligence. This book aims to achieve the objectives and present the concepts and applications of digital marketing in the age of artificial intelligence to readers in a comprehensive manner. The book highlights the major breakthroughs and technologies in digital marketing for effective interaction, analysis, prediction and design to formulate the best strategy for a business, using artificial intelligence solutions. This enables specialists to apply advances in digital marketing in the age of artificial intelligence in the right way to serve customers and solve business problems in this competitive age. Covering the intersection of marketing and artificial intelligence, this book is a first-rate reference and an indispensable resource for business leaders, academics, salespeople, marketing professionals, managers, business owners, researchers, practitioners, instructors, college and university libraries, students, consultants, businesspeople, computer scientists, and customer-focused institutions.."-- Provided by publisher.
Keywords: Internet marketing.; Artificial intelligence.; elektronické knihy; electronic books